Respuesta :
Step-by-step explanation:
[tex]6 {i}^{955} = 6 {i}^{954 + 1} \\ \\ = 6 {i}^{954} \times {i} \\ \\ = 6( {i}^{2} )^{477} \times i \\ \\ = 6( - 1)^{477}\times i ... (\because i^2 =-1)\\ \\ = 6 \times ( - 1) \times i\\... (\because 477\:is \: an \:odd \:number) \\ \\ = - 6i\\\\\huge \purple {\boxed {\therefore 6 {i}^{955} =-6i}} [/tex]
Answer:
-6i
Step-by-step explanation:
6×i⁹⁵⁵
Every fourth power of i is +1
i.e i⁴ = +1
i⁹⁵⁵ = i⁹⁵² × i³ (separating multiples of 4 in the power)
i⁹⁵² = +1 because 952 is multiple of 4
i⁹⁵⁵ = +1 × i³
i³ = -i
i⁹⁵⁵ = +1 × -i = -6
So,
6i⁹⁵⁵ = 6 × -i = -6i